Kedudukan Dan Materi Muatan Peraturan Menteri Dalam Perspektif Sistem Presidensial - Ni'matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2021)
The obesity of regulations at the central and regional levels lead to problems in structuring legislation. The various ministerial regulations make it difficult for local governments to follow up. The problems studied in this research are first, what is the position and content of ministerial regulations in the perspective of legislation and the presidential system in Indonesia? Second, how to avoid obesity in the formation of ministerial regulations in the administration of government? The two problems will be analyzed in descriptive-qualitative manner, using statutory and conceptual approaches. The results of this study conclude that first, ministerial regulations are essentially not included in the hierarchy of laws and regulations, yet they can be issued by the minister as long as there is an authority or order from a higher law to regulate it and only applies internally for the benefit of the present institution. However, the ministers in the presidential system are not responsible to the parliament but to the president, hence the right person to stipulate the laws and regulations should be the president; second, to avoid the occurrence of obesity in the formation of ministerial regulations, the president only needs to form a Government Regulation or Presidential Regulation, and does not need to delegate it to the minister to form implementing regulations.